Parenting Patterns Related to the Incidence of Stunting in Early Childhood - Rahayu Ningsih; Heru Subaris Kasjono; Siswanto Pabidang (GLOBAL HEALTH SCIENCE GROUP, 2026)
Stunting is a serious problem faced by many developing countries, including Indonesia. This condition occurs when a child experiences stunted growth due to chronic malnutrition, characterized by a child's height being shorter than children of the same age. Stunting is influenced by various factors, namely lack of access to nutritious food, lack of knowledge about nutrition and health, poor sanitation, and poverty. The purpose of the study was to determine the relationship between Parenting Patterns with the Incidence of Stunting in Early Childhood. The type of research used is a study. observational analytic with cross sectional approach . Subjects in this study included toddlers aged 06-59 months in Teluk Rumbia Village. The sampling technique in this study used purposive sampling using the Slovin formula. The research instrument used a questionnaire. All questionnaires tested showed a calculated r value (see the corrected item-total correlation column) of 0.444, indicating that all questionnaires were valid. The reliability value for the 10 questions on parenting patterns was 0.850 0.60. EPPGBM Application and Checklist Sheet. Data Analysis using Chi Square. Characteristics with Poor Parenting Patterns were 19 people (33.9%) and Good Parenting Patterns were 37 people (66.1%). Respondents had characteristics of Not Stunting as many as 29 people (51.8%) and those who were not stunted as many as 27 people (48.2%). The parenting factor obtained a p-value of 0.006 < 0.05, which means there is a meaningful relationship. The strength of the relationship shown from the OR result is Parenting Patterns (OR: 0.384), Mother's parenting patterns are related to the incidence of stunting in Teluk Rumbia Village. This study is expected to provide practical guidance for parents in Teluk Rumbia Village in improving childcare patterns to prevent stunting.